Communal roosting, thermoregulatory benefits and breeding group size predictability in cooperatively breeding sociable weavers - Matthieu Paquet; Claire Doutrelant; Maxime Loubon; Franck Theron; Margaux Rat; Rita Covas (Journal of Avian Biology, 2016)
Extreme temperatures impose energy costs on endotherms through thermoregulation and different adaptations help individuals to cope with these conditions. In social species, communal roosting and huddling are thought to decrease the energetic requirement of thermoregulation under low temperatures. This is likely to represent an important mechanism by which individuals save energy during the coldest parts of the year and hence to represent a non‐breeding benefit of sociality. Here, we investigate the potential thermoregulatory benefits of group living in roosting groups of sociable weavers Philetairus socius, a colonial cooperatively breeding passerine that builds communally a massive nest structure with several independent chambers wherein individuals breed and roost throughout the year. To investigate the benefits of sociality during the non‐breeding season, we studied the thermal environment during roosting in relation to group size. In addition, to understand the link between non‐breeding and breeding sociality in this species we studied group size stability between the pre‐breeding and breeding periods. As expected, we found that the nest chamber's night‐time temperature is strongly related to the number of birds roosting together, especially during cold nights. Specifically, birds in larger groups spent less time below the critical thermal minimum temperature (i.e. the temperature below which energy expenditure increases substantially). They were less exposed to external temperature variations. We also found a positive relationship between the number of birds roosting during winter and the breeding group size, indicating breeding group size predictability. In cooperative breeders such as the sociable weaver, the costs and benefits of sociality are usually studied during the breeding period. This study shows that a better understanding of non‐breeding benefits of group membership and group dynamics between the non‐breeding and breeding periods are necessary for a comprehensive understanding of the benefits of sociality.